Investigating the Relationship Between Digital Game Addiction and Health-related Quality of Life of Adolescents - Alev Ustundag; Vildan Caymaz (Gonabad University of Medical Sciences, 2024)
Background: Adolescence is one of the most important developmental processes in one's life, and the habits gained during this period are likely to continue throughout life. This study determines whether there is a relationship between the digital game addiction levels of adolescents and their quality of life (QoL). Methods: This is a quantitative study with a relational screening model. It was conducted in Ankara Province, Turkey, and involved 650 adolescents aged 14-18 years, selected via the simple random sampling method in the 2022-2023 school year. The personal information form, KINDL QoL scale, and digital game addiction scale were used to collect the data. The data were analyzed using point double series correlation analysis and Pearson correlation analysis test.  Results: The results showed that adolescents had a moderate QoL (Mean±SD 49.98±8.92), and they were in the risk group for digital game addiction (Mean±SD 44.6±17.51). There was no significant relationship between the QoL of the adolescents participating in the research and the levels of digital game addiction, except other than a significant, positive, and low-level relationship between the QoL and the emotion change and immersion, sub-dimension of the digital game addiction scale (r=0.079, P<0.005). In addition, there was a significant and positive relationship between the QoL, and a significant, positive, and moderate relationship between digital game addiction levels and gender of the adolescents (rpb=0.131, P<0.001; rpb=0.377, P<0.001). Conclusion: Precautions should be taken immediately because of the increased risk of addiction to digital games.